Binocular saccade coordination in reading and visual search: a developmental study in typical reader and dyslexic children - Seassau, Magali; Gérard, Christophe Loic; Bui-Quoc, Emmanuel; Bucci, Maria Pia (Frontiers in Integrative Neuroscience, 2014)
Studies dealing with developmental aspects of binocular eye movement behavior during reading are scarce. In this study we have explored binocular strategies during reading and visual search tasks in a large population of dyslexic and typical readers. Binocular eye movements were recorded using a video-oculography system in 43 dyslexic children (aged 8 to 13) and in a group of 42 age-matched typical readers. The main findings are (i) ocular motor characteristics of dyslexic children are impaired in comparison to those reported in typical children in reading task ; (ii) a developmental effect exists in reading in control children; in dyslexic children the effect of development was observed only on fixation durations ; (iii) ocular motor behavior in the visual search tasks is similar for dyslexic children and for typical readers, except for the disconjugacy during and after the saccade: dyslexic children are impaired in comparison to typical children. Data reported here confirms and expands previous studies on children’s reading. Both reading skills and binocular saccades coordination improve with age in typical readers. The atypical eye movement’s patterns observed in dyslexic children suggest a deficiency in the visual attentional processing as well as an impairment of the ocular motor saccade and vergence systems interaction.